H∞- optimal controller design using genetic algorithms - Phàn, Vũ Ngọc (Journal of Computer Science and Cybernetics, 2016)
The goal of the present paper is to verify the possibility of genetic algorithms for solving the H∞-optimal controller design problem. After formulating the design problem in Section 2 and repeating the background of genetic algorithms in Section 3, some simulation results using MATLAB 5.2 will be explained in Section 4; In Section 5 the method will be shortly discussed.